Patch grafting of organoids of stem/progenitors into solid organs can correct genetic-based disease states. (September 2022) - Zhang, Wencheng; Wauthier, Eliane; Lanzoni, Giacomo; Hani, Homayoun; Yi, Xianwen; Overi, Diletta; Shi, Lei; Simpson, Sean; Allen, Amanda; Suitt, Carolyn; Ezzell, Jennifer Ashley; Alvaro, Domenico; et al.
Abstract: Patch grafting, a novel strategy for transplantation of stem/progenitor organoids into porcine livers, has been found successful also for organoid transplantation into other normal or diseased solid organs in pigs and mice. Each organoid contained ∼100 cells comprised of biliary tree stem cells (BTSCs), co-hepato/pancreatic stem/progenitors, and partnered with early lineage stage mesenchymal cells (ELSMCs), angioblasts and precursors to endothelia and stellate cells. Patch grafting enabled transplantation into livers or pancreases of ≥10 8th (pigs) or ≥10 6th−7th (mice) organoids/patch. Graft conditions fostered expression of multiple matrix-metalloproteinases (MMPs), especially secretory isoforms, resulting in transient loss of the organ's matrix-dictated histological features, including organ capsules, and correlated with rapid integration within a week of organoids throughout the organs and without emboli or ectopic cell distribution. Secondarily, within another week, there was clearance of graft biomaterials, followed by muted expression of MMPs, restoration of matrix-dictated histology, and maturation of donor cells to functional adult fates. The ability of patch grafts of organoids to rescue hosts from genetic-based disease states was demonstrated with grafts of BTSC/ELSMC organoids on livers, able to rescue NRG/FAH-KO mice from type I tyrosinemia, a disease caused by absence of fumaryl acetoacetate hydrolase. With the same grafts, if on pancreas, they were able to rescue NRG/Akita mice from type I diabetes, caused by a mutation in the insulin 2 gene. The potential of patch grafting for cell therapies for solid organs now requires translational studies to enable its adaptation and uses for clinical programs. Abstract : Patch grafting enables transplantation of large numbers of epithelia (>10 8th cells), ideally as organoids of epithelial and mesenchymal stem/progenitors, and results within a week in their rapid integration amidst host cells throughout a solid organ. The strategies are successful with every solid organ tried, even pancreas, notorious for its propensity for autolysis with cell therapy attempts. Patch grafting succeeds in normal and diseased organs and so does not require regenerative forces in the host organ for engraftment to occur. Patch grafted donor stem/progenitors matured to functional cells able to rescue hosts from genetic-based diseases such as type I tyrosinemia and type I diabetes.